Efficacy of nanomicelle curcumin, Nigella sativa oil, and their combination on bone turnover markers and their safety in postmenopausal women with primary osteoporosis and osteopenia: A triple‐blind randomized controlled trial. Issue 2 (30th November 2021) - Kheiridoost, Hanie; Shakouri, Seyed Kazem; Shojaei‐Zarghani, Sara; Dolatkhah, Neda; Farshbaf‐Khalili, Azizeh
Abstract: Literature supports the potential effects of nanomicelle curcumin and Nigella sativa on the amelioration of osteoporosis, a health concern of postmenopausal women. This study aimed to evaluate the impacts of nanomicelle curcumin (CUR), Nigella sativa oil (NS), and their combination on bone turnover biomarkers and assess their safety. This triple‐blind randomized controlled trial was performed on 120 postmenopausal women aged 50–65 with primary osteoporosis or osteopenia. The subjects were randomly allocated to receive microcrystalline cellulose (placebo), 80 mg of CUR, 1000 mg of NS, or their combination (CUR‐NS) for 6 months. All patients were also treated with alendronate (70 mg) and calcium (500 mg), vitamin D (400 IU) supplements. The serum levels of alkaline phosphatase (ALP), osteocalcin (OC), and osteopontin (OP) were measured at the baseline and after the intervention. For safety assessment, the hepatic enzyme levels of aspartate transaminase and alanine transaminase as well as serum urea and creatinine were evaluated. ALP levels were significantly reduced in the NS ( p  = .029) and CUR‐NS ( p  = .015) groups compared with those in the placebo. After adjustment for the covariates, this effect was still significant in the CUR‐NS group ( p  = .004). The OC levels were decreased in the placebo, CUR, and NS groups, and the OP concentration also was attenuated in all groups through the trial. However, the intergroup differences were not significant for both biomarkers. Evaluating the key renal metabolites and hepatic enzyme levels indicated no toxicity of the administered doses. This study reveals the beneficial effects of CUR‐NS on the improvement of some bone turnover biomarkers. These compounds seem to be safe at the current dosage for supplementation in postmenopausal women. Abstract : This study reveals the beneficial effects of nanomicelle curcumin and Nigella sativa oil on the improvement of some bone turnover biomarkers. These compounds seem to be safe at the current dosage for supplementation in postmenopausal women.